2006
DOI: 10.1017/s1743921306003036
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the chemical inhomogeneity of PNe with VLT FLAMES integral-field unit spectroscopy

Abstract: Abstract. Recent weak emission-line long-slit surveys and modelling studies of PNe have convincingly argued in favour of the existence of an unknown component in the planetary nebula plasma consisting of cold, hydrogen-deficient gas, as an explanation for the long-standing recombination-line versus forbidden-line temperature and abundance discrepancy problems. Here we describe the rationale and initial results from a detailed spectroscopic study of three Galactic PNe undertaken with the VLT FLAMES integral-fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 7 publications
(9 reference statements)
6
27
1
Order By: Relevance
“…In particular, the O ii flux map seems to peak at the position of the apex of HH 202, the zone also known as HH 202‐S – spaxels (−5.5, −6.5) and (−6.5, −4.5). A similar spatial distribution of both kinds of lines was already observed using long‐slit spectra in the Orion Nebula by Mesa‐Delgado et al (2008), as well as in the three PNe observed by Tsamis et al (2008). Fig.…”
Section: Line Measurements and Reddening Correctionsupporting
confidence: 83%
See 2 more Smart Citations
“…In particular, the O ii flux map seems to peak at the position of the apex of HH 202, the zone also known as HH 202‐S – spaxels (−5.5, −6.5) and (−6.5, −4.5). A similar spatial distribution of both kinds of lines was already observed using long‐slit spectra in the Orion Nebula by Mesa‐Delgado et al (2008), as well as in the three PNe observed by Tsamis et al (2008). Fig.…”
Section: Line Measurements and Reddening Correctionsupporting
confidence: 83%
“…This apparent trend is mainly produced by the behaviour observed at HH 202‐S and HH 202‐N, which are precisely the zones where the O 2+ and C 2+ abundances obtained from RLs are lower and T e ([O iii ]) is higher. From integral field spectroscopy, Tsamis et al (2008) have found rather clear positive correlations between ionic abundances obtained from RLs and T e in three PNe, exactly the opposite trend we observe in this FOV of the Orion Nebula. These authors argue that their results provide evidence for the existence of two distinct components of highly ionized gas at very different temperatures.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, only a small number of PNe have been studied using a spectroscopic mapping technique. Some examples are NGC 6369 (Monteiro et al 2004), NGC 40 (Leal-Ferreira et al 2011, NGC 5882 (Tsamis et al 2008), NGC 6153 (Tsamis et al 2008), and NGC 7009 (Tsamis et al 2008;Phillips et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral H 2 imaging in the infrared has been applied mostly to map the morphology of post-AGB stars and the AGB remnant halo of Planetary Nebulae (Hrivnak et al 2008(Hrivnak et al , 2006Sahai & Trauger 1998;Kastner et al 2001;Cox et al 2003;Davis et al 2005; Van de Steene et al 2008). The novel technique of Integral Field Spectroscopy has been applied for these evolved objects to obtain higher spatial and spectral resolution in molecular hydrogen and other lines (Tsamis et al 2008;Sandin et al 2008;Santander-García et al 2007Sharp et al 2006;Lowe & Gledhill 2006;Monreal-Ibero et al 2005).…”
Section: The Molecular Envelopesmentioning
confidence: 99%